Microstructure evolution of an artificially aged Al-Zn-Mg-Cu alloy subjected to soft- and hard-steel core projectiles - Muhammad Abubaker Khan; Yangwei Wang; Huanwu Cheng; Ghulam Yasin; Abdul Malik; Faisal Nazeer; Tahir Ahmad; Waheed Qamar khan; Muhammad Kamran; Mohamed A. Afifi (Journal of Materials Research and Technology, 2020)
An investigation was conducted to study the effect of soft (220 Hv) and hard (750 Hv) steel projectiles on an Al-Zn-Mg-Cu alloy processed by hot extrusion followed by heat treatment (solid solution treatment at 743 K/1.5 h + ageing treatment at 388 K/24 h). The results show that the hardness of the projectile material can influence on the shape and size of the perforation channel formed after the penetration. The hard steel projectile has longer depth of penetration and the crater front diameter is narrower comparing with the Al alloy after penetration by the soft steel projectile. Adiabatic shear bands (ASBs) are formed in the perforation channel after penetration with presence of recrystallized grains within these bands. The ASBs are wider after the hard steel projectile penetration with presence of cracks comparing with the ASBs formed after the soft steel projectile penetration. Precipitates are increased in size and overlapped in the perforation channel which are mainly of G.P. zone and η' precipitates. Hardness values of the Al alloy after penetration increase in the upper side of the perforation channel over the middle and end regions of the channel.